Study on Functioning of Efferent Auditory Pathway in Mentally Challenged - Yerraguntla, K; Vanila, VJ; Bellur, R (Nepalese Journal of ENT Head and Neck Surgery, 2012)
Nepalese Journal of ENT Head and Neck Surgery Vol.2 No.1 Issue 1 (Jan-Jun 2011) 5-7 DOI: http://dx.doi.org/10.3126/njenthns.v2i1.6775